Adaptive multimodal user interface techniques for mobile augmented reality: Frameworks, modalities and user interaction - Arvind Ramtohul; Kavi Kumar Khedo (Array)
Mobile augmented reality (MAR) has revolutionised information perception and real-world interaction. The introduction of MAR has enriched users’ visualisation abilities, enabling them to understand complex objects and reveal previously inaccessible aspects. However, traditional MAR systems predominantly rely on unimodal interaction techniques and the exploitation of user and contextual data has been moderate. This leads to inadequate interaction with augmented content ultimately impacting the user experience and engagement negatively. To address these shortcomings, adaptive multimodal user interface (AMUI) techniques in MAR have emerged, offering refined interaction mechanisms by leveraging multiple modalities and incorporating user and contextual information. In this paper, a systematic review of the adaptive and multimodal literature in MAR is conducted, aiming to assess the impact of AMUI techniques in MAR systems. This paper provides a comprehensive examination of the current state of AMUI-MAR systems and frameworks and identifies key research issues requiring further investigation. The findings of this paper have demonstrated that AMUI techniques have significant potential and can transform the interaction landscape of MAR, offering enhanced user experience and engagement. By leveraging multiple interaction modalities and better utilizing user and contextual information, AMUI techniques can pave the way for more natural and intuitive interactions in MAR.